The influence of security, ease of use, and privacy concern on repurchase intention with e-satisfaction as a mediation on e-commerce - Yunia Tessa Lolika (Operations Management and Information System Studies, 2021)
The purpose of this study was to analyze: (1) the effect of security on repurchase intention on Shopee users. (2) effect of ease of use on repurchase intention of Shopee users, (3) effect of privacy concern on repurchase intention of Shopee users, (4) effect of security on e-satisfaction on Shopee users, (5) effect of ease of use on e-satisfaction on Shopee users, (6) effect of privacy concern on e-satisfaction on Shopee users, (7) effect of e-satisfaction on repurchase intention for Shopee users, (8) the mediation role of e-satisfaction between security and repurchase intention, (9) the mediation role of e-satisfaction between ease of use and repurchase intention, (10) mediation role of e-satisfaction between privacy concern and repurchase intention. The population in this study were all Shopee users in Padang City who had shopped more than twice. The number of samples in this study was 200 respondents. Data was collected through the distribution of online questionnaires and data processing was carried out through SmartPLS software. The results of this study indicate that (1) security has a positive and significant effect on Repurchase Intention, (2) ease of use has a positive and significant effect on repurchase intention, (3) privacy concern has a positive and significant effect on repurchase intention, (4) security has a positive and significant effect on e-satisfaction, (5) ease of use has a positive and significant effect on e-satisfaction, (6) privacy concern has a positive and significant effect on e-satisfaction, (7) e-satisfaction has a positive and significant effect on repurchase intention, (8) e-satisfaction significantly mediates the relationship between security and repurchase intention, (9) e-satisfaction significantly mediates the relationship between ease of use and repurchase intention, (10) e-satisfaction significantly mediates the relationship between privacy and repurchase intention.